Depressive symptoms are related to asthma control but not self-management among rural adolescents - Patel, Neha B.; Céspedes, Amarilis; Liu, Jianfang; Bruzzese, Jean-Marie (Frontiers in Allergy, 2024)
Background Depression, a relevant comorbidity with asthma, has been reported to be associated with asthma morbidity. Asthma self-management is essential to asthma control and may be negatively impacted by depression. We examined these associations in rural adolescents, a group with relatively high asthma morbidity and depressive symptoms, a population often ignored in asthma research. Methods We used baseline data from a randomized trial of an asthma intervention for adolescents in rural South Carolina (n = 197). Adolescents completed the Center for Epidemiological Studies-Depression (CES-D), three indices of asthma self-management (the Asthma Prevention Index, the Asthma Management Index and the Asthma Self-Efficacy Index), and the Asthma Control Test (ACT). Poisson and linear regression tested associations between depression, self-management, and asthma control. The models controlled for demographic variables and included school as a fixed effect. Results Most participants (mean age = 16.3 ± 1.2 years) self-identified as female (68.5%) and Black (62.43%). The mean CES-D score was 19.7 ± 10.3, with 61.4% of participants at risk for depression. The depressive symptoms were significantly related to asthma control [β = −0.085, 95% confidence interval (CI) = −0.14 to −0.03] but not to prevention [relative risk (RR) = 1.00, 95% CI = 0.99–1.01], management (RR = 1.00, 95% CI = 0.99–1.01), or self-efficacy (β = −0.002, 95% CI = −0.01 to 0.01), Conclusions In this sample of rural adolescents, as depressive symptoms increased, asthma control declined. Depressive symptoms were not associated with asthma self-management, suggesting that the aspects of self-management we assessed are not an avenue by which depression impacts asthma control. Additional research is needed to further understand the relationship between depressive symptoms, asthma self-management, and control.